Experimental Stroke Differentially Affects Discrete Subpopulations of Splenic Macrophages - McCulloch, Laura; Alfieri, Alessio; McColl, Barry W. (Frontiers in Immunology, 2018)
Changes to the immune system after stroke are complex and can result in both pro-inflammatory and immunosuppressive consequences. Following ischemic stroke, brain resident microglia are activated and circulating monocytes are recruited to the injury site. In contrast, there is a systemic deactivation of monocytes/ macrophages that may contribute to immunosuppression and the high incidence of bacterial infection experienced by stroke patients. The manipulation of macrophage subsets may be a useful therapeutic strategy to reduce infection and improve outcome in patients after stroke. Recent research has enhanced our understanding of the heterogeneity of macrophages even within the same tissue. The spleen is the largest natural reservoir of immune cells, many of which are mobilised to the site of injury after ischemic stroke and is notable for the diversity of its functionally distinct macrophage subpopulations associated with specific micro-anatomical locations. Here we describe the effects of experimental stroke in mice on these distinct splenic macrophage subpopulations. Red pulp (RP) and marginal zone macrophages (MZM) specifically showed increases in density and alterations in micro-anatomical location. These changes were not due to increased recruitment from the bone marrow but may be associated with increases in local proliferation. Genes associated with phagocytosis and proteolytic processing were upregulated in the spleen after stroke with increased expression of the lysosome-associated protein LAMP2 specifically increased in RP and MZM subsets. In contrast, MHC class II expression was reduced specifically in these populations. Furthermore, genes associated with macrophage ability to communicate with other immune cells, such as co-stimulatory molecules and inflammatory cytokine production, were also downregulated in the spleen after stroke. These findings suggest that selective splenic macrophage functions could be impaired after stroke and the contribution of macrophages to stroke-associated pathology and infectious complications should be considered at a subset-specific level. Therefore, optimal therapeutic manipulation of macrophages to improve stroke outcome is likely to require selective targeting of functionally and spatially distinct subpopulations.